ANALISIS KESULITAN BELAJAR SISWA KELAS III MELALUI PENDEKATAN TEMATIK DI UPT SDN 61 GRESIK - Sadiah, Muslikhatus; Windasari, Windasari; Khamidi, Amrozi (IKIP PGRI Bojonegoro, 2024)
This study aims to determine the learning difficulties in thematic learning experienced by third grade students and the factors that influence thematic learning difficulties at UPT SDN 61 Gresik. This research uses a type of qualitative research with a descriptive approach, data collection techniques in this study, namely using observation and interview methods with the subjects of this research, namely the third grade homeroom teacher, third grade teacher, and 5 third grade students at UPT SDN 61 Gresik. In this study, the results obtained regarding the types of learning difficulties experienced by students are, 1) Difficulty finding material, 2) Thematic lesson hours are too long, 3) Lack of learning motivation, 4) Low student thinking power, 5) Crowded classroom atmosphere, 6) Difficulty in certain subjects. Meanwhile, the factors that influence student learning difficulties are, 1) One theme book, 2) Students' capacity to accept learning, 3) Student age, 4) The role of parents, 5) The classroom atmosphere is not conducive. The conclusion of learning difficulties for primary level students is a pr for teachers in creating a learning atmosphere that is easily accepted by students. Keywords: Learning Difficulties; Primary School; Students; Thematic